Pluralizing Frameworks for Global Ethics in the Internationalization of Higher Education in Canada - Stein, Sharon; Andreotti, Vanessa; Suša, Rene (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
Internationalization continues to be a priority within many Canadian universities. While it is imperative to attend to the ethical dilemmas that accompany the intensification of internationalization, different ethical frameworks operate according to different orientating assumptions. In this paper, we seek to pluralize and deepen conversations about the ethics of internationalization by illustrating how three global ethics approaches address questions of international student mobility, study and service abroad, and internationalizing the curriculum. We conclude by emphasizing the need for both scholars and practitioners to engage in multi-voiced, critically-informed analyses, and dissensual conversations about complex ethical dilemmas related to internationalization.